Mitochondrial ATP-Dependent K⁺ Channels Downregulate Ionotropic Glutamate Receptors During Hypoxia in Retinal Horizontal Cells of Goldfish - Ramadan, Mohamed (Université d'Ottawa / University of Ottawa, 2025)
Retinal neurons rely on a continuous supply of oxygen to maintain function, yet some species like goldfish can withstand prolonged hypoxic periods due to adaptations that remain unclear. Horizontal cells (HCs) are interneurons in the retina that shape visual signalling by feeding back to photoreceptors. In the present study, we investigated whether ionotropic glutamate receptors (iGluRs) in goldfish HCs are suppressed during hypoxia and whether this process is mediated by mitochondrial ATP-sensitive K⁺ (mK_ATP) channel activation. Through perforated patch-clamp electrophysiology, we determined that glutamate application under hypoxia reduced median peak current density by ~10.5% (P = 0.0059), whereas control recordings in normoxia showed stable responses. When mK_ATP channels were blocked with 100 μM glibenclamide during hypoxia, the suppressed response was abolished. Inhibiting mitochondrial calcium (Ca²⁺) uptake via the mitochondrial Ca²⁺ uniporter (MCU) with ruthenium red and blocking Ca²⁺ release through ryanodine receptors in the endoplasmic reticulum also abolished the hypoxia-induced suppression. Taken together, these results indicate that mK_ATP activation triggers a controlled Ca²⁺ signal that downregulates iGluR activity in the membrane. Through the reduction of receptor activity, HCs may lower their metabolic demand, allowing them to maintain cell function during hypoxia. The proposed mechanism can ultimately provide insight into treating retinal conditions associated with hypoxia such as retinal ischemia and stroke.
Keywords: retina; horizontal cell; goldfish; ionotropic glutamate receptor; mKATP; hypoxia; calcium; excitotoxicity; GABA